Pengaruh Model Discovery Learning terhadap Pemahaman Konsep Perkalian dan Pembagian Pecahan Kelas V SD - Rahma, Aminatu; Masniladevi, Masniladevi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
One of the learning models that can be applied in mathematics learning is the Discovery Learning model. This study aims to determine the effect of the Discovery Learning model on understanding the concept of multiplication and division of fractions in grade V SD. This type of research is quantitative with Quasi Experiment Design with the type of Non-equivalent Control Group Design. The research subjects were fifth grade students of SDN 05 Maninjau, Tanjung Raya District. Based on the calculation of the t-test results data analysis with a significant level of 0.05 and dk = n1 + n2 - 2 = 17 + 20 - 2 = 35, obtained tcount (2.49) and t table (1.68957). So that tcount> ttable, where 2.49> 1.68975. Thus it can be concluded that there is an effect of the Discovery Learning model on understanding the concept of multiplication and division of fractions in grade V SD.